Pengaruh Pemahaman Akuntansi Berbasis SAK-ETAP , Computer Self-Efficacy dan Komitmen Organisasi Terhadap Efektivitas Pelaporan Keuangan Pada Koperasi Simpan Pinjam di Kecamatan Buleleng - Ayunda Prihantini; I Gusti Ayu Purnamawati (Universitas Pendidikan Ganesha, 2022)
This study aims to determined the effect of accounting understanding based on SAK-ETAP, computer self-efficacy and organizational commitment on the effectiveness of financial reporting. This research was conducted with quantitative methods, namely primary data obtained from questionnaire data which was measured using a Likert scale. This research was conducted at the Savings and Loans Cooperative in Buleleng District. The sampling method was carried out by purposive sampling method, obtained a sample of 16 Savings and Loans Cooperatives that were still active with 48 employees of Savings and Loan Cooperatives as respondents. Data analysis in this study used descriptive analysis, data quality test, classical assumption test, multiple linear regression analysis, and hypothesis testing with the help of SPSS version 24.0 for windows. Based on the results of the analysis of this study, the results showed that (1) understanding of accounting based on SAK-ETAP has a positive and significant effect on the effectiveness of financial reporting, (2) computer self-efficacy has a positive and significant effect on the effectiveness of financial reporting, (3) organizational commitment has an effect on the effectiveness of financial reporting. positive and significant on the effectiveness of financial reporting. Keywords: SAK-ETAP, Computer self-efficacy, Organizational commitment, Effectiveness Financial Reporting